Memory a mediator between test-anxiety and academic achievement in high school students. - Yousefi, Fayegh; Mansor, Mariani; Juhari, Rumaya; Redzuan, Marof; Abu Talib, Mansor; Kumar, Vijay; Naderi, Habibollah (European Journals Inc., 2009)
The purpose of study was to investigate the relationship between test-anxiety and GPA through memory in high school students. The sample was 400 students (200 male and 200 female) in the age range of 15-19 years. The instrument used for data collection was the Test-Anxiety Inventory (TAI). An analysis of the data obtained from the current study showed that, for the respondents, test-anxiety had a significant impact on grade point average (GPA) through memory (z=1.93, p== 0.02). Given the results of the study, it is recommended that academic achievement and mental health be developed in school settings, through the use of support strategies such as educational guidance and counseling, teaching life skill programs and psychotherapy.